Latin America: The Region without Catalonia - Rudowski, Tomasz; Sieniawski, Piotr (International Studies. Interdisciplinary Political and Cultural Journal, 2020)
The aim of this article is to analyse the issue of “weak separatism” in Latin America as well as to give an answer to the question why there are no significant separatist movements in this region. The authors provide the definitions of separatism and secessionism as well as an explanation of these phenomena. Moreover, they present an overview of historical and contemporary separatist movements in Latin America. Based on Horowitz’s theory of ethnic separatism, the authors attempt to analyse the separatist movement “The South is My Country” in Brazil and compare it with separatism in Catalonia in Spain, where a referendum on independence from Spain was held in 2017, serving as an impetus for a similar referendum that took place in the South of Brazil. In spite of similar goals of these two separatist movements, the authors argue that there are significant differences in their nature, which are determined by the history and culture of the respective countries.